Formation of incipient anodes in localized mortar repairs with the addition of rice husk silica - Remenche, Igor Rossi; Daschevi, Paulo Augusto; Holowka, Nikolai Franceschetto; Martioli, Leonardo Caniato; Farias de Medeiros, Marcelo Henrique (Revista ALCONPAT, 2024)
The objective of this work was to investigate how incipient anodes can be detected and monitored in localized repair areas using mortars with added rice husk silica. Three repair conditions were tested on prismatic specimens: without repair, with repair without rice husk silica addition, and with rice husk silica addition in the mortar. Corrosion potential and electrical resistivity tests were conducted. The corrosion potential test showed no variation along the bar, while the electrical resistivity test showed varied values depending on the repaired and non-repaired zones. It was concluded that adding rice husk silica to the mortar made the corrosion potential more electronegative due to the greater difference in electrical resistivity compared to the substrate, contributing to the formation of incipient anodes.